θ-Centralizers on Semiprime Banach *-algebras - Nikoufar, I.; Rassias, J. M. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We generalize the celebrated theorem of Johnson and prove that every left θ -centralizer on a semisimple Banach algebra with left approximate identity is continuous. We also investigate the generalized Hyers–Ulam–Rassias stability and the superstability of θ -centralizers on semiprime Banach *-algebras.